Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 5 - Review Exercises - Page 400: 29



Work Step by Step

Given:$f(x)=x^2-7x+2$ Plug $x=(a-1)$ in above equation, we have $f(a-1)=(a-1)^2-7(a-1)+2=a^2-9a+10$ Now, $f(a+h)-f(a)=[(a+h)^2-7(a+h)+2]-[a^2-7a+2]$ This gives $=h^2+2ah-7h$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.